The ultraviolet responses of ZnO-based thin-film transistor prepared by sol–gel method. (December 2015) - Zhang, M.; Yu, Z. N.; Wang, J. Z.; Xue, W.
Abstract : Bottom-gate and top-contact thin-film transistors with ZnO film as a channel layer were fabricated by sol–gel method. The structural and optical properties of the deposited ZnO films were investigated through X-ray diffractometer, scanning electron microscopy and UV–Vis spectrophotometer. ZnO film has a high absorption in the ultraviolet region and c -axis orientation normal to the substrate. The on/off current ratio, channel mobility and threshold voltage of ZnO-based thin-film transistors in dark are 10 5, 0·02 cm 2  V −1  s −1 and 8·3 V, respectively. Under UV light illumination ( λ  = 365 nm) with an intensity of 2·4 μW/cm 2, the drain–source current I DS of thin-film transistor dramatically increases and the photo-to-dark current ratio is greater than 10 4 . The transient response of the device to ultraviolet illumination is also discussed. The results may open the possibility of employing ZnO-thin-film transistors as UV photodetector.